Aneurin Bevan - Michael Foot; FOOT (Michael) (London Granada Publishing, 1979)
An abridged version of Michael Foot's biography of Labour leader Aneurin Bevan, published to commemorate the centenary of his birth. Bevan died in 1960, and was acclaimed by all sides as a great politician. Throughout his life he was at the centre of controversy, seemingly at war with leaders of all political parties, including his own.
Keywords: Biography; Socialist